2019
DOI: 10.1016/j.firesaf.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Progressive collapse analysis of composite steel frames subject to fire following earthquake

Abstract: This paper presents three-dimensional progressive collapse analyses of composite steel frames exposed to fire following earthquake. The scenarios of heating columns located in various different fire compartments (internal, edge and corner bay) are first studied to investigate load redistribution paths and members' interactions within the composite frame. The results show that the loads previously supported by the heated columns are redistributed to adjacent columns along two horizontal directions, a phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…1: (Boguslawski et al , 2016); 2: (Vandecasteele et al , 2017); 3: (Li et al , 2014); 4: (Olenick and Carpenter, 2003); 5: (Cheng et al , 2016); 6: (Wang et al , 2015); 7: (Wu and Chen, 2012); 8: (Zverovich et al , 2016); 9: (Zverovich et al , 2017); 10: (Yang et al , 2013); 11: (Drysdale, 2011); 12: (Osman and Ram, 2013); 13: (Lurz et al , 2017); 14: (Hsu et al , 2014); 15: (Xu et al , 2016); 16: (Isikdag et al , 2013); 17: (Sattar et al , 2018); 18: (Shen et al , 2008); 19: (Kang et al , 2016); 20: (Groner et al , 2012); 21: (Shi et al , 2009); 22: (Harris, 2013); 23: (Porcari et al , 2015); 24: (Suwondo et al , 2019); 25: (Mould, 2001); 26: (Knyziak et al , 2019); 27: (Naser, 2019); 28: (Shan et al , 2019); 29: (Yuen et al , 2014); 30: (Rüppel and Schatz, 2011); 31: (Cheng et al , 2018); 32: (Thompson and Marchant, 1995); 33: (Qiao et al , 2012); 34:(Averill, 2011); 35: (“SFPE_HumanBehavior_Guide_fir.pdf”, 2017); 36: (National Iranian Gas Company, 2013); 37: (Iran National Regulatory Office, 2013); 38: (Emergency exit routes, 2003); 39: (Richardson et al , 2019); 40: (Till and Coon, 2018); 41: (Xie et al , 2018); 42: (García-Hernández et al , 2019); 43: (Chou et al , 2019); 44: (Li et al , 2014); 45: (Evans et al , 2019); 46: (Bandyopadhyay and Mukherjee, 2016); 47: (Ohta and Dunkel, 2019); 48: (NFPA 1500, 2007); 49: (Pope and Bailey, 2006); 50: (Mirahadi et al , 2019); 51: (Kinsey et al , 2019); 52: (Chen et al , 2018); 53: (Zhang and Issa, 2015); 54: (Boguslawski et al , 2018); 55: (Xu et al , 2018); 56: (Boje et al , 2018); 57: (Smith and Brokaw, 2008); 58: (Park et al , 2017); 59: (Wagner and Agrawal, 2014); 60: (Cocking et al , 2009); 61: (Davies et al , 2009); 62: (Venkatesh et al , 2019); 63: (Fahy et al , 2017);64: (Kasereka et al , 2018); 65: (…”
Section: Figurementioning
confidence: 99%
“…1: (Boguslawski et al , 2016); 2: (Vandecasteele et al , 2017); 3: (Li et al , 2014); 4: (Olenick and Carpenter, 2003); 5: (Cheng et al , 2016); 6: (Wang et al , 2015); 7: (Wu and Chen, 2012); 8: (Zverovich et al , 2016); 9: (Zverovich et al , 2017); 10: (Yang et al , 2013); 11: (Drysdale, 2011); 12: (Osman and Ram, 2013); 13: (Lurz et al , 2017); 14: (Hsu et al , 2014); 15: (Xu et al , 2016); 16: (Isikdag et al , 2013); 17: (Sattar et al , 2018); 18: (Shen et al , 2008); 19: (Kang et al , 2016); 20: (Groner et al , 2012); 21: (Shi et al , 2009); 22: (Harris, 2013); 23: (Porcari et al , 2015); 24: (Suwondo et al , 2019); 25: (Mould, 2001); 26: (Knyziak et al , 2019); 27: (Naser, 2019); 28: (Shan et al , 2019); 29: (Yuen et al , 2014); 30: (Rüppel and Schatz, 2011); 31: (Cheng et al , 2018); 32: (Thompson and Marchant, 1995); 33: (Qiao et al , 2012); 34:(Averill, 2011); 35: (“SFPE_HumanBehavior_Guide_fir.pdf”, 2017); 36: (National Iranian Gas Company, 2013); 37: (Iran National Regulatory Office, 2013); 38: (Emergency exit routes, 2003); 39: (Richardson et al , 2019); 40: (Till and Coon, 2018); 41: (Xie et al , 2018); 42: (García-Hernández et al , 2019); 43: (Chou et al , 2019); 44: (Li et al , 2014); 45: (Evans et al , 2019); 46: (Bandyopadhyay and Mukherjee, 2016); 47: (Ohta and Dunkel, 2019); 48: (NFPA 1500, 2007); 49: (Pope and Bailey, 2006); 50: (Mirahadi et al , 2019); 51: (Kinsey et al , 2019); 52: (Chen et al , 2018); 53: (Zhang and Issa, 2015); 54: (Boguslawski et al , 2018); 55: (Xu et al , 2018); 56: (Boje et al , 2018); 57: (Smith and Brokaw, 2008); 58: (Park et al , 2017); 59: (Wagner and Agrawal, 2014); 60: (Cocking et al , 2009); 61: (Davies et al , 2009); 62: (Venkatesh et al , 2019); 63: (Fahy et al , 2017);64: (Kasereka et al , 2018); 65: (…”
Section: Figurementioning
confidence: 99%
“…This study adopted an in-plane finite element model of the case study frame for its simplicity and computational time; however, it is essential to note such a model ignores the out-of-plane redistribution of forces observed in experimental and 3-D numerical investigations (Suwondo et al, 2019). Also, the reinforced cement concrete (RCC) slab's beneficial effects due to the composite action between steel and concrete and the tension field action of the RCC slab cannot be realized in a two-dimensional model.…”
Section: Jsfe 124mentioning
confidence: 99%
“…However, global stability was not compromised in either fire scenario (Behnam and Rezvani, 2016). In another study, Suwondo et al (2019) considered a three-dimensional finite element model of a composite steel building for conducting a series of progressive collapse analyses in the FO and PEF scenarios. The residual deformation in the frame and the fire compartment's damage, which may alter the building's fire propagation, was studied.…”
mentioning
confidence: 99%
“…More recent studies have developed 3D frame models to study the robustness of steel frames with composite slabs in fire situations (Agarwal & Varma, 2014; Jiang and Li, 2017a, 2017b; Suwondo et al, 2019). The results showed that 3D models predict different collapse modes and load redistribution paths compared to those of 2D frames.…”
Section: Introductionmentioning
confidence: 99%